The Survey of Outcomes and Return to Game in Score Player with Reconstructed Anterior Cruciate Ligament - Ali Golchini; Nasser Beh-Pour; Shahram Ahanjan; Morteza Saeb; Saeed Soleimani (University of Social Welfare and Rehabilitation Sciences, 2014)
Objective: The purpose of the study was to evaluate the outcomes and back to the sport in soccer players with anterior cruciate ligament (ACL) reconstruction during one year. Materials & Methods: 32 soccer players who underwent reconstruction of ACL via BPTBG (Bony-Patellar Tendon-Bony graft) (Technique Modified Clancy) selected and randomly divided into two 16-subject traditional and accelerated groups. The accelerated group performed the accelerated rehabilitation protocol for 24 weeks and the traditional group were performed a traditional rehabilitation program for a period of 36 weeks. At the end of the 4th, 6th, 9th and 12th months, the knee muscular function, subjective performance and time period of returning to sport competitions was evaluated. A repeated measure ANOVA and t test were used for data analyzing at 0.05 levels. Results: In both groups, the muscular function of operated extremity was less than healthy ones. The function of the operated knee in accelerated group was significantly better than the traditional group (p<0.05). In both scales (lysholm and Cincinnati), the subjective performance of accelerated group was higher than traditional group (p&le0.05). Accelerated group, returned to 3 and 4 competition levels whereas this level in traditional group was significantly lower (1 and 2), (p&le0.02). Conclusion: The result showed that any deficit in strength has a strong relationship with failure in soccer player's athletic performance and causes a decline in individual's subjective function. Also the accelerated exercise programs (neuromuscular) play a significant role in a more safe return of the soccer players to the competition.